Neurocognitive profiles and thrombogenic inhibitors (TAFI, TFPI) in apparently asympomatic individuals with cerebral small vessel disease - Zaki, Zakiyyah Munirah Mohd (2018)
Cerebral small vessel disease (CSVD) is the term coined to address the many abnormal presentations of the brain under neuroimaging techniques. White matter hyperintensities (WMH), one of the most common appearance seen under normal healthy populations which often described as normal appearing white matter becomes a concern as it posed a detrimental effect on cognitive functions as well as gait and motor abilities, culminating a huge burden to the society economically. There are various causal factors suggested to contribute in pathogenesis of this silent yet progressive disease. Among the main pathways hypothesized are the coagulation/complement, inflammation, signal transduction and lipid metabolism. This current study aims to determine the relationship between CSVD in healthy individuals, and the selected blood biomarkers particularly thrombogenic inhibitors (TAFI and TFPI) as well as neurocognitive profiles. This was an exploratory study from random selection of subjects recruited from Klinik Rawatan Keluarga, Hospital Universiti Sains Malaysia. An online-based cardiovascular risk calculator (QRISK2) was also used for risk prediction. Those who met the inclusion and exclusion criteria were recruited and underwent MRI brain scanning (Phillips 3-Tesla Achieva MR Scanner), blood sampling and neuropsychological performance based on Wechsler Adult Intelligent Scale IV (WAIS-IV). The baseline MRI images were used to group the subjects based on the presence of white matter hyperintensities (WMHs) scored by Fazekas scale. Blood plasma was used to determine the thrombogenic factors (TAFI, TFPI) by using ELISA and seven subtests of WAIS IV were taken for neuropsychological testing Block Design, Matrix Reasoning and Visual Puzzle; Digit Span and Letter-Number Sequencing; Coding and Symbol Search for three different main cognitive domains Perceptual Reasoning, Working Memory and Processing Speed, respectively. The analyses were done by performing statistical test using IBM SPSS Statistics version 24.0. A total of thirty-three (N=33) subjects recruited with QRISK2 score <20%, aged between 25 to 62 years old, with similar distribution of 30% male and 70% female at both baseline and follow up. Upon MRI scanning, 15 (45.5%) were detected with WMH at baseline however only 11 (40.7%) of them came back for follow up at one-year. The mean age was 39 years old (range from 25 to 62 year old. TFPI at follow up was seen to be significantly increased meanwhile TAFI was higher at baseline point. However, only TFPI at follow up contributed to the association model of WMH outcome [B=-3.964, Wald 5.106, OR= 0.021, p<0.05]. Comparing both groups together, only TFPI showed significant changes between WMH+ and WMH- at follow up. The neurocognitive profiling shows association between PSI with age, QRISK2 score and PRI with p value 0.003, 0.016 and 0.018 respectively, however no cognitive domains show any association or predictive value to the WMH outcome. Interestingly, WMI and TFPI at follow up show a significant correlation with p<0.05. The result suggests that only TFPI is associated with presence of WMH, coupled with changes in PSI. As for TAFI, despite a decreased level within a year, its role is probably not apparent in the early stage of CSVD. Finally, the study has also established a selected cohort of at-risk asymptomatic CSVD individuals within our local population for future studies, including to further elucidate the role of emerging or novel biomarkers for CSVD.